Pierwsza powieść – ostatnia szczerość? O debiutanckiej powieści Elizy Orzeszkowej „Ostatnia miłość" - Kreft, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
Eliza Orzeszkowa’s first novel Ostatnia Miłość (Last Love) from 1867 is a piece now almost forgotten. The article presents the circumstances in which the work was born and its biographical background. As an example of committed literature, this seemingly banal romance hides an interesting subtext. The analysis of the novel’s motifs leads to a conclusion about its deeper-than-expected ties to Orzeszkowa’s biography. Behind the mask of widely-known facts from her life, the young writer unconsciously exposes her genuine feelings and beliefs which would soon become suppressed for many years to come by her officially-proclaimed dedication to the cause, the necessity to make sacrifices, and commitment to her responsibilities. The work was written before Orzeszkowa developed a system of self-controlled sincerity, which is why the title of the article asks whether the first novel was her last burst of genuineness and confession of the truth about her dreams for many years.